The Problem with David: Masculinity and Morality in Biblical Cinema - MacGeough, Kevin (The journal of religion and film, 2018)
The King David of the Bible, and especially as portrayed in the books of Samuel, is one of the most complex characters in ancient literature. We are told his story from his youth as a shepherd until his death as king of Israel. He kills a mighty warrior with a slingshot, goes to war with his king and later his son, and has an affair that threatens to throw his kingdom into disarray. The stories surrounding David seem perfect for cinematic adaptation yet what makes this character so compelling has been problematic for filmmakers. Here, three types of Biblical filmmaking shall be considered: Hollywood epics (David and Bathsheba (1951), David and Goliath (1960), and King David (1985)); televised event series (The Story of David (1976) andThe Bible: The Epic Miniseries (2013)); and independent Christian films (David and Goliath (2015) and David vs. Goliath: Battle of Faith (2016)). Issues that shall be considered include: tone and genre, casting, democracy and ideology, masculinity, and sexual morality. This investigation shall explore how these issues are treated in different types of Biblical filmmaking and how genre constraints impact the reception of David on film.